2012
DOI: 10.1111/jbg.12021
|View full text |Cite
|
Sign up to set email alerts
|

Genetic parameters for birthweight environmental variability in mice

Abstract: Data from a divergent experiment for birthweight (BrW) environmental variability were used to estimate genetic parameters for BrW trait and its environmental variability by fitting both homoscedastic (HO) and heteroscedastic (HE) models. A total of 5 475 records of BrW from animals born from inbred dams, and 7 140 pedigree records were used. The heritability of BrW using the model HO was 0.27, with the litter effect much more important, 0.43. The model HE provided a genetic correlation between the trait and it… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
33
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(33 citation statements)
references
References 33 publications
0
33
0
Order By: Relevance
“…There is some evidence in several species that environmental variance can be under genetic control, although only two selection experiments to investigate this have been performed, both using selection for birth weight, in mice [22] and rabbits [21]. A major problem in analyzing environmental variance comes from the complexity of the models that are often used, which are highly parametrized and have nested effects and parameters.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is some evidence in several species that environmental variance can be under genetic control, although only two selection experiments to investigate this have been performed, both using selection for birth weight, in mice [22] and rabbits [21]. A major problem in analyzing environmental variance comes from the complexity of the models that are often used, which are highly parametrized and have nested effects and parameters.…”
Section: Discussionmentioning
confidence: 99%
“…Most of this evidence is indirect, because it comes from analyses of databases and not from experiments designed to assess the genetic determination of environmental variance (litter size in sheep [10] and pigs [11], birth weight and stillbirth in pigs [12], weight in snails [13], birth weight in mice [14], uterine capacity in rabbits [15], weight in poultry [16] and beef cattle [17], milk yield of dairy cattle [18], and weight in trout [19] and salmon [20]). Other evidence of the existence of a genetic component for environmental variance comes from a few experiments on inbred lines of Drosophila melanogaster [1] and from only two selection experiments on birth weight, in rabbits [21] and mice [22]. Models used to analyze environmental variance were reviewed by Hill and Mulder [23].…”
Section: Introductionmentioning
confidence: 99%
“…Pun et al . () designed a genetic divergent selection experiment in mouse to assay by selecting the environmental variability of the birth weight. However, this experiment failed, because as the authors argued, the trait was attributed to the individual when it should have been assigned to the mother (Pun et al .…”
Section: Introductionmentioning
confidence: 99%
“…First, genetic parameters were estimated. In this case, most of the estimates were obtained by using maternal models because previously published results (Pun et al, 2013) showed the convenience of analysing BW environmental variability as a maternal trait. The maternal heritability obtained for the traits were within the range of previous results published on mice (Ibáñez-Escriche et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…The three-way cross-population was previously maintained in panmixia during 40 generations ensuring high levels of both genetic and phenotypic variability. This high-variability population was also the origin for other selection experiments (Fernández et al, 1998;Gutiérrez et al, 2006;Ibáñez-Escriche et al, 2008;Moreno et al, 2011;Pun et al, 2013). To set up the low and high-variability lines, initially a total of 64 males and females were randomly mated one male to one female having two litters in order to evaluate the mothers for the environmental BW variability of their offspring.…”
Section: Datamentioning
confidence: 99%